Analisis Kebijakan Deviden dan Struktur Modal pada Kinerja Keuangan Perusahaan Umum Daerah Air Minum Kota Makassar - Serina Ayu; Nurhadi; Muhammad Akbardin (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the effect of dividend policy and capital structure on the financial performance of the Regional Public Water Supply Company (PDAM) of Makassar City. This research uses a quantitative descriptive approach by analyzing secondary data obtained from the company’s financial statements for the period 2021–2023. The analysis employs financial ratios, including Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER), Return on Assets (ROA), Net Profit Margin (NPM), and Current Ratio (CR). The results show that PDAM Makassar City implements a moderate dividend policy, as indicated by a DPR of 63% in 2023, while maintaining a conservative capital structure with a consistently low DER. Financial performance, measured through ROA and NPM, shows fluctuations but remains at a relatively healthy level, supported by strong liquidity reflected in a high CR. Overall, the findings indicate that a balanced dividend policy and prudent capital structure contribute positively to the company’s financial performance and sustainability of public services.